2018
DOI: 10.14712/18059694.2018.122
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Children with Juvenile Psoriatic Arthritis

Abstract: Background: To evaluate the presence of endothelial dysfunction in Slovak children with juvenile psoriatic arthritis in the absence of classic cardiovascular risk factors in order to assess its relationship to the disease activity and disability. Methods: 25 juvenile psoriatic arthritis patients (JPSA) and 25 healthy controls aged 6–19 years were enrolled into this study. In all subjects vascular measurements over a period of three years (January 2013 – January 2016) were performed, in accordance with the guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…A total of 9 studies [ 17 , 19 , 20 , 22 , 26 , 28 , 30 32 ] surveyed the association between TC and JIA. The heterogeneity result ( P = 0.000, I 2 = 76.1%) showed that there was some homogeneity in the research literature, and the random effect model was utilized for combined statistics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 9 studies [ 17 , 19 , 20 , 22 , 26 , 28 , 30 32 ] surveyed the association between TC and JIA. The heterogeneity result ( P = 0.000, I 2 = 76.1%) showed that there was some homogeneity in the research literature, and the random effect model was utilized for combined statistics.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies (1739) were eliminated during the initial screening process based on their titles and summaries. Out of the 155 full-text studies that were scrutinized, only 16 studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] satisfied the predetermined inclusion criteria (Fig. 1; Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…В ряде исследований продемонстрировано, что степень эндотелиальной дисфункции коррелирует со степенью тяжести псориаза и является более выраженной при ранней манифестации заболевания [43]. Даже при отсутствии дополнительных факторов риска патологические процессы в сосудистой стенке (воспаление, нарушения ангиогенеза) предрасполагают к развитию атеросклероза и сердечно-сосудистых болезней у пациентов с псориазом [43,44]. Показано, что пациенты с псориазом имеют склонность к формированию уплотнений и кальцификатов в сосудистой стенке, что также служит независимым риском атеросклеротического поражения [45,46].…”
Section: сердечно-сосудистые заболеванияunclassified